Paracetamol-induced liver injury modelled in Xenopus laevis embryos. (1st March 2019) - Saide, Katy; Sherwood, Victoria; Wheeler, Grant N.
Highlights: Drug induced liver injury is a major reason for compound drop-out during drug development. Xenopus embryos provide a useful in vivo model to study drug toxicity. Xenopus embryos exhibit similar reactions to paracetamol induced liver injury observed in mammalian models. Abstract: Introduction: Failure to predict drug-induced liver injury (DILI) remains a major contributing factor to lead compound drop-out during drug development. Xenopus embryos are amenable for early stage medium throughput small molecule screens and so have the potential to be used in pre-clinical screens. To begin to assess the usefulness and limitations of Xenopus embryos for safety assessment in the early phases of drug development, paracetamol was used as a model hepatotoxin. Paracetamol overdose is associated with acute liver injury. In mammals, the main mechanism of paracetamol-induced acute liver injury is an increased amount of the reactive metabolite N -acetyl-p-benzoquinone imine (NAPQI) combined with a reduction of free glutathione (GSH). Humans that have taken an overdose of paracetamol are often treated with N- acetyl cysteine (NAC). Method: Xenopus laevis embryos were treated with up to 5 mM paracetamol from stage 38 to stage 45 during development, when the liver is functional. The presence of paracetamol-induced liver injury was assessed by: (1) microRNA-122 (miR-122) expression (a hepatic marker), (2) free GSH concentration (a marker of oxidative stress) and (3) NAC antioxidant intervention. Results: The amount of free GSH decreased significantly in embryos exposed to increasing paracetamol concentration. In embryos exposed to 5 mM paracetamol, 22.57 ± 4.25 nmol/mg GSH was detected compared to 47.11 ± 7.31 nmol/mg untreated embryos (mean ± SEM). In tail tissue, miRNA-122 expression increased 6.3-fold with 3 mM paracetamol concentration treatment compared to untreated embryos. NAC treatment altered the free GSH decline for embryos treated with up to 5 mM. Embryos exposed to 1 mM paracetamol and then exposed to 0.5 mM NAC 24 h prior to harvest, had a significantly higher amount of GSH compared to embryos that were only exposed to 1 mM paracetamol (mean ± SEM; 97.1 ± 9.6 nmol/mg and 54.5 ± 6.6 nmol/mg respectively). Conclusion: Xenopus laevis embryos exhibit similar characteristics of paracetamol-induced liver injury observed in mammalian models. These data indicate that the Xenopus embryo could be a useful in vivo model to assess DILI and aid lead compound prioritisation during the early phase of drug development, in combination with pre-clinical in vitro studies. Consequently, the Xenopus embryo could contribute to the reduction principle as defined by the National Centre for the Replacement, Refinement and Reduction of Animals in Research.